Cognitive impairment in a rat model of neuropathic pain: role of hippocampal microtubule stability. Issue 8 (August 2018) - You, Zerong; Zhang, Shuzhuo; Shen, Shiqian; Yang, Jinsheng; Ding, Weihua; Yang, Liuyue; Lim, Grewo; Doheny, Jason T.; Tate, Samuel; Chen, Lucy; Mao, Jianren
Abstract : Abstract: Clinical evidence indicates that cognitive impairment is a common comorbid condition of chronic pain. However, the cellular basis for chronic pain–mediated cognitive impairment remains unclear. We report here that rats exhibited memory deficits after spared nerve injury (SNI). We found that levels of stable microtubule (MT) were increased in the hippocampus of the rats with memory deficits. This increase in stable MT is marked by α-tubulin hyperacetylation. Paclitaxel, a pharmacological MT stabilizer, increased the level of stable MT in the hippocampus and induced learning and memory deficits in normal rats. Furthermore, paclitaxel reduced long-term potentiation in hippocampal slices and increased stable MT (evidenced by α-tubulin hyperacetylation) levels in hippocampal neuronal cells. Intracerebroventricular infusion of nocodazole, an MT destabilizer, ameliorated memory deficits in rats with SNI-induced nociceptive behavior. Expression of HDAC6, an α-tubulin deacetylase, was reduced in the hippocampus in rats with cognitive impairment. These findings indicate that peripheral nerve injury (eg, SNI) affects the MT dynamic equilibrium, which is critical to neuronal structure and synaptic plasticity. Abstract : Supplemental Digital Content is Available in the Text.Peripheral nerve injury affects hippocampal microtubule dynamic equilibrium, which is critical to neuronal structure and synaptic plasticity.